35 Long-term Improvements in Site-Rated Outcomes with Deutetrabenazine Treatment in Patients with Tardive Dyskinesia. (12th March 2019) - Anderson, Karen E.; Stamler, David; Davis, Mat D.; Gross, Nicholas; Hauser, Robert A.; Jarskog, L. Fredrik; Jimenez-Shahed, Joohi; Kumar, Rajeev; Ochudlo, Stanislaw; McEvoy, Joseph; Fernandez, Hubert H.
Abstract: Background: Tardive dyskinesia (TD) is an often-irreversible movement disorder that may intensify the stigma of patients with psychiatric disorders and worsen quality of life. In two randomized, double-blind, placebo (PBO)-controlled, 12-week trials, ARM-TD and AIM-TD ('parent studies'), deutetrabenazine (DTB) demonstrated statistically significant improvements in centrally read Abnormal Involuntary Movement Scale (AIMS) scores at Week 12 compared with PBO and was generally well tolerated. Study Objective: To evaluate the long-term efficacy of DTB in an open-label safety study following double-blind treatment using site-rated efficacy measures: AIMS, the Clinical Global Impression of Change (CGIC) and the Patient Global Impression of Change (PGIC), which may be used in real-world clinical practice settings. Method: Patients with TD who completed the parent studies were eligible to enter this open-label, long-term extension (OLE) after completing the 1-week washout period and final evaluation in the blinded portion of the trial. This extension comprised a 6-week titration period followed by a long-term maintenance phase. Patients began DTB at 12mg/day, titrating up to a maximum total dose of 48mg/day based on dyskinesia control and tolerability. Efficacy endpoints included in this analysis are the change in site-rated AIMS score (items 1–7) from parent study baseline, and the proportion of patients who were "Much Improved" or "Very Much Improved" (treatment success) on the CGIC and PGIC from OLE baseline. Results: At the end of the parent studies (Week 12), patients treated with DTB had experienced greater mean (standard error) improvements in site-rated AIMS score (–5.0[0.40]) than patients given PBO (–3.2[0.47]). With long-term DTB treatment, both groups experienced improvements in site-rated AIMS scores (prior DTB, –7.9[0.62]; prior placebo, –6.6[0.64]) compared with parent study baseline. Similarly, at the end of the parent studies, a greater proportion of patients treated with DTB had treatment success on the CGIC (DTB, 51%; PBO, 32%) and the PGIC (DTB, 46%; PBO: 33%); whereas at Week 54 of the OLE study, treatment success on CGIC and PGIC were similar in both the CGIC (prior DTB: 66%; prior PBO: 68%) and PGIC (prior DTB: 62%; prior PBO: 62%) groups. DTB was generally well tolerated. Conclusions: Patients treated with DTB showed improvements in abnormal movements, as measured by site-rated AIMS, CGIC, and PGIC scores, which may be used in real-world clinical practice settings. These results corroborate the previously reported efficacy of DTB as observed in the 12-week, double-blind ARM-TD and AIM-TD trials, in which central raters were used to evaluate AIMS scores. Presented at: American Psychiatric Association Annual Meeting; May 5–9, 2018, New York, New York, USA Funding Acknowledgements: Funding: This study was supported by Teva Pharmaceuticals, Petach Tikva, Israel.